Teaching knowledge and vocational training: the importance of the relationship between daily knowledge and school knowledge in teaching and mathematical learning in basic education (Research, Society and Development, 2022)
The study is the result of an investigation into teaching knowledge and the training of teachers in the teaching of mathematics, present for the importance of the relationship between everyday knowledge and school knowledge in and in the learning of mathematics. It aimed to investigate whether professional training can help the teacher in the relationship between everyday knowledge and school knowledge in the process of teaching and learning mathematics. We take as theoretical reference the studies of Freire (1996), Lorenzato (2010), Gauthier (1998), Ribeiro (1997), Franchi (1995), Nogueira et al. (2014), Andrade (2013) and PCNs of Mathematics (Brasil, 1998). We used bibliographic research, appropriating qualitative methods with analysis and discussion, relying on reading, reflection and dialogue. The results show that teachers who educated little in forming the challenge of qualified teachers for the student of reality are inserted, therefore, a great educator is in the practice of including school contents with reality, finding himself as a teacher to be a teacher if that mathematics education, in order to be more effective, takes into account the importance of the discipline and the contents of the reality and interest of the students, since its contents, I teach teaching in an individualized way, do not become an effective tool for solving problems and for the construction of new concepts. Thus, the relationship between school knowledge and everyday knowledge becomes not so important, but necessary for teaching and learning.